Search for signatures of extra dimensions in the diphoton mass spectrum at the large hadron collider - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
A search for signatures of extra spatial dimensions in the diphoton invariant-mass spectrum has been performed with the CMS detector at the LHC. No excess of events above the standard model expectation is observed using a data sample collected in proton-proton collisions at √s=7TeV corresponding to an integrated luminosity of 2.2fb -1. In the context of the large-extra-dimensions model, lower limits are set on the effective Planck scale in the range of 2.3-3.8TeV at the 95% confidence level. These limits are the most restrictive bounds on virtual-graviton exchange to date. The most restrictive lower limits to date are also set on the mass of the first graviton excitation in the Randall-Sundrum model in the range of 0.86-1.84TeV, for values of the associated coupling parameter between 0.01 and 0.10. © 2012 CERN, for the LHCb Collaboration. Published by the American Physical Society under the terms of the Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published articles title, journal citation, and DOI.